Protein kinase C activity and hexamethylenebisacetamide-induced erythroleukemia cell differentiation. - Melloni, E (1987)
Hexamethylenebisacetamide (HMBA) is a potent inducer of murine erythroleukemia (MEL) cell differentiation. The mechanism of action of HMBA is not known. In this study we provide evidence that protein kinase C has a role in inducer-mediated MEL cell differentiation: (i) HMBA induces the formation of a soluble, proteolytically activated form of protein kinase C that is catalytically active in the absence of Ca2+ and phospholipid; (ii) the protease inhibitor leupeptin blocks formation of this activated form of the kinase and inhibits HMBA-induced MEL cell hemoglobin accumulation; (iii) phorbol 12-myristate 13-acetate (PMA) inhibits HMBA-induced MEL differentiation and causes depletion of total protein kinase C activity; (iv) MEL cells depleted in protein kinase C activity by culture with PMA are resistant to induction by HMBA; (v) upon removal of PMA, restoration of MEL cell sensitivity to HMBA is correlated with reaccumulation of protein kinase C activity; and (vi) MEL cells grown to density arrest are both depleted of protein kinase C activity and resistant to HMBA. Together, these results suggest that HMBA-mediated MEL cell differentiation involves a protein kinase C-related mechanism and the proteolytically activated form of the kinase, which does not require Ca2+ or phospholipid for its catalytic activity.